2022
DOI: 10.3390/ijms23148003
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Villous Differentiation and Placental Development

Abstract: In humans, the placenta provides the only fetomaternal connection and is essential for establishing a pregnancy as well as fetal well-being. Additionally, it allows maternal physiological adaptation and embryonic immunological acceptance, support, and nutrition. The placenta is derived from extra-embryonic tissues that develop rapidly and dynamically in the first weeks of pregnancy. It is primarily composed of trophoblasts that differentiate into villi, stromal cells, macrophages, and fetal endothelial cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 167 publications
(136 reference statements)
0
10
0
2
Order By: Relevance
“…This is an intriguing phenomenon. Previous studies have demonstrated that the presence of stromal cells surrounding placental villi plays a crucial role in stimulating angiogenesis in the placenta 31 . And the placental vascular development can significantly impact placental function, subsequently leading to fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an intriguing phenomenon. Previous studies have demonstrated that the presence of stromal cells surrounding placental villi plays a crucial role in stimulating angiogenesis in the placenta 31 . And the placental vascular development can significantly impact placental function, subsequently leading to fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the presence of stromal cells surrounding placental villi plays a crucial role in stimulating angiogenesis in the placenta. 31 And the placental vascular development can significantly impact placental function, subsequently leading to fetal growth restriction. In cases of severe fetal growth restriction, it has been observed that matrices derived from placental stromal cells impaired fetoplacental angiogenesis.…”
Section: Genesmentioning
confidence: 99%
“…Placental pathologies leading to FGR can occur at any step of the complex placental development. Often, the placenta shows reduced volume, surface and vascularization in fetuses with growth restriction, which can be due to the malregulation of certain molecular pathways [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extravillous trophoblasts (EVTs) are the dominant cell type involved in the process of placentation, invading deeply into the maternal decidua and uterine blood vessels, dissolving the extracellular matrix, remodeling the uterine vasculature, and coming into direct contact with the maternal decidua immune cells (DICs). The precise regulation of EVT invasion and remodeling of spiral arteries are key events of placentation [ 1 ]. As a result of placentation, the maternal immune system has to adapt to tolerate the semi-allogeneic fetus while maintaining maternal immune competence.…”
Section: Introductionmentioning
confidence: 99%